Blastocystis across humans, animals and the environment in rural Türkiye, and relationships with the human intestinal microbiome - Akdur-Öztürk, Eylem; Al-Adilee, Yaseen Majid Salman; Edwards, William; Gentekaki, Eleni; Tsaousis, Anastasios D.; Dogruman-Al, Funda (Frontiers in Microbiology, 2025)
Blastocystis is a globally prevalent intestinal protist commonly found in humans and animals, yet its role in health and disease remains ambiguous. This is a cross-sectional study of Blastocystis in rural Türkiye, examining 124 human, 305 livestock (cattle, sheep, goats), and 40 environmental samples using culture/microscopy, qPCR, and sequencing. We further explored associations between Blastocystis and population parameters, along with gut microbiota profiles. Using a combination of sequencing and microscopy, the overall prevalence was high, at 76.6% in humans, 71%–78% in livestock, and 38% in environmental samples. Subtypes ST1–ST4 were detected in humans, with ST3 being most frequent. Livestock harbored ST10 predominantly, with goats showing high carriage of ST24. Several subtypes (e.g., ST25, ST26) were recorded in livestock for the first time in Türkiye. Body mass index (BMI) was significantly associated with Blastocystis colonization, with lean individuals having higher carriage. Contrary to other studies, individuals with ST4 exhibited reduced bacterial diversity and altered microbial composition, suggesting subtype-specific interactions. By combining parasitology, microbiome, and environmental analysis, this study offers an overview of Blastocystis diversity and distribution in rural Türkiye. This work provides a foundation for future integrative research approaches to explore the ecological role of Blastocystis and its subtypes, potential health implications, and interactions with other microbes in rural and global contexts.